2021
DOI: 10.4103/ija.ija_237_21
|View full text |Cite
|
Sign up to set email alerts
|

Baska Mask is non-inferior to tracheal tube in preventing airway contamination during controlled ventilation in elective nasal surgeries: A randomised controlled trial

Abstract: Background and Aims: Baska Mask, a newly designed third-generation supraglottic device, has a sump where the pharyngeal secretions can collect and be suctioned out continuously. We aimed to study the effectiveness of Baska Mask in preventing airway contamination during nasal surgeries. Our primary objective was to assess airway soiling using fibreoptic bronchoscopy. Total airway manipulation time, haemodynamic parameters during device insertion and post-operative oro-pharyngeal morbidities were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A previous study reported that the Baska mask demonstrated a level of utility comparable to that of SAD. Many studies have also been conducted to evaluate the effectiveness of the Baska mask compared to other airway devices [ 7 9 , 17 24 ]. In most studies, the Baska mask was considered an appropriate SAD for maintaining stable hemodynamics, effective tidal volume, and suitable airway pressures.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the Baska mask demonstrated a level of utility comparable to that of SAD. Many studies have also been conducted to evaluate the effectiveness of the Baska mask compared to other airway devices [ 7 9 , 17 24 ]. In most studies, the Baska mask was considered an appropriate SAD for maintaining stable hemodynamics, effective tidal volume, and suitable airway pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this, it has been equipped with a gastric reflux high-flow suction clearance system. [ 27 ] Another inclusion is the LMA protectorÔ. Distinct from other SADs, it contains two gastric drainage channels and a pharyngeal chamber to drain the gastric contents.…”
Section: Newer Tools and Techniques For Airway Managementmentioning
confidence: 99%
“…The most interesting is the advances in the supraglottic airway devices with enhanced protection against aspiration which may be comparable to the ETT (51). In the management of patients with VFI, using these devices would avoid contact with the implant.…”
Section: Future Directionsmentioning
confidence: 99%